Sentencing Reform in Canada: Recent Developments - Roberts, Julian; von Hirsch, Andrew (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1992)
Changes to the sentencing process in Canada are finally imminent. A number of reports in recent years have called for reforms in the area of sentencing and parole. In 1987, the Canadian Sentencing Commission released its final report Sentencing Reform: A Canadian Approach. This was followed in 1988 by the report of the Daubney Committee following its investigation into sentencing and parole. In addition to these proposals, the now-defunct Law Reform Commission of Canada, the Department of Justice and the Ministry of the Solicitor General all published reports containing reform proposals. In this article, the authors review recent events in the area of sentencing since the publication of the report of the Canadian Sentencing Commission. After a brief introduction, four principal policy issues are examined: (i) statutory statements of sentencing purpose; (ii) sentencing guidelines; (iii) the future of release on parole; (iv) the creation of a permanent sentencing commission for Canada. For each issue, the article critically examines the position taken by major players in the area of criminal law reform. The article concludes with a brief examination of Bill C-90, which recently received first reading, and which will be the object of further parliamentary scrutiny in the fall of 1992. In a subsequent article, the authors offer their own proposals to reform the sentencing of offenders in Canada.